Pengaruh Nisbah Kelamin Parasitoid Cotesia flavipes Cam. (Hymenoptera : Braconidae) dan Ukuran Panjang Inang Chilo sacchariphagus Boj. (Lepidoptera : Crambidae) terhadap Fekunditas yang Dihasilkan di Laboratorium - Andrico Tampubolon; Marhenit Marheni; Darma Bakti (Universitas Sumatera Utara, 2015)
The objective of the research was to study the effect of sex ratio Cotesia flavipes and the length hostof C. sacchariphagus on the resulting fecundity. The research was conducted at the Laboratory ofSugarcane Research and Development Sei Semayang, Binjai, Medan, North Sumatera from Marchuntil May 2014. This method used Randomized Complete Design Factorial with two factors.The first factor was sex ratio of C. flavipes (0 male : 1 female ; 1 male : 1 female ;1 male : 2 females ; 1 male : 3 females ; 1 male : 4 females) and the second factor was size ofC. Sacchariphagus (<1.5 cm ; >1.5 cm - < 2.0 cm ; > 2.0 cm ) with three replications.The resultsshowed that the percentage of parasititation depend on host size of C. sacchariphagus. The highestpercentage of parasititation (40%) was on the big size of C. sacchariphagus (> 2.0 cm) and thelowest (0%) was on the small size of C. sacchariphagus (<1.5 cm). Sex ratio significantly effectedon the number of female C. flavipes. The highest number of female C. flavipes (13.11 head) on1 male : 4 females and the lowest (0 head) on 1 female : 0 male. Sex ratio of male and femalewas 2.48 : 1.Keywords : Cotesia flavipes, host size, sex ratio, Chilo sacchariphagus